HOUNSFIELD UNIT (HU) VALUE ANALYSIS ON CT-SCAN STONOGRAPHY EXAMINATION IN UROLITHIASIS - Cahyati, Yeni; NRPK, Noeki (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2025)
Abstract Background: The use of CT-Scan is an examination of the urinary tract or what is usually called a non-contrast urography CT-Scan or CT-Scan Stonography. CT-Scan Stonography is a CT-Scan examination of the kidney tract which is usually used to detect the presence of stones in the kidneys. Stonography is used as an alternative to IVP (Intravenous Pyelography) examination because the IVP examination is limited in providing information to diagnose a disease, especially in cases of urolithiasis. In CT-Scan stonography examinations, the Hounsfield Unit (HU) value plays an important role in diagnosing abnormalities in the urinary system. The Hounsfield Unit (HU) value is the density level of various types of tissue which has 4,096 shades of gray, and has different density levels. differences found in CT-Scan. In establishing a diagnosis in patients with clinical urolithiasis or abnormalities in the presence of stones in the urinary system which are formed from crystals of Ca Oxalate, Ca Phosphate, Strufit stones, Cystine stones, and uric acid stones, the use of HU values helps in measuring the density value of the stones so that treatment can be estimated. that will be given to the patient. Objective: The aim of this study is to determine the Hounsfield Unit (HU) value in clinical urolithiasis using CT-Scan Stonography examination. Method: This research is a qualitative descriptive study, namely by carrying out CT-Scan stonography examinations on urolithiasis patients and analyzing the results of measuring Hounsfield Unit (HU) values. Results: Based on 10 research data results, the characteristics of stone composition based on Hounsfield Unit (HU) value analysis on 10 samples were categorized into 3 groups, namely, the calcium phosphate stone group consisting of 3 samples, cystine stone consisting of 5 samples, and 2 samples on uric acid stone group. Conclusion: Hounsfield Unit (HU) value to determine further medical action